Fingerprinting of Bacterial Genomes by Amplification of DNA Fragments Surrounding Rare Restriction Sites - Aleksander Masny; Andrzej Plucienniczak (BioTechniques)
A method for generating limited representations of total bacterial DNA, without prior knowledge of the DNA sequence, has been developed. This method consists of three steps: digestion with two restriction enzymes, ligation of two oligonucleotide adapters corresponding to the restriction sites, and selective PCR amplification of the ligation products. The method relies on the use of two restriction enzymes with considerable differences in cleavage frequency of the investigated DNA and the ligation of two different oligonucleotides, each corresponding to one of the two cohesive ends of DNA fragments. Three subsets of DNA fragments are generated during digestion and subsequent ligation: terminated with the same oligonucleotide on both 5′ ends of DNA fragments (two subsets) and terminated with two different oligonucleotides. Suppression PCR allows only the third subset of DNA fragments to be amplified exponentially. The method allows bacterial species strain differentiation on the basis of the different DNA band patterns obtained after electrophoresis in polyacrylamide gels stained with ethidium bromide and visualized in UV light.